Ultrasonic‑assisted molten salt hydrates pretreated Eucheuma cottonii residues as a greener precursor for third-generation l-lactic acid production. (November 2022) - Chong, Soo Ling; Tan, Inn Shi; Foo, Henry Chee Yew; Chan, Yen San; Lam, Man Kee; Lee, Keat Teong
Graphical abstract: Highlights: Coupling of ZnCl2 and ultrasonication promoted the removal of recalcitrant ECRs. Highest L-LA yield (90.08%) through SHF was archieved from hydrolysates of P-ECRs. Nutrient combination act as yeast extract substitution for lactic acid bacteria. Abstract: This study aims to establish an efficient pretreatment method that facilitates the conversion of sugars from macroalgae wastes, Eucheuma cottonii residues (ECRs) during hydrolysis and subsequently enhances l -lactic acid (L-LA) production. Hence, ultrasonic-assisted molten salt hydrates (UMSHs) pretreatment was proposed to enhance the accessibility of ECRs to hydrolyze into glucose through dilute acid hydrolysis (DAH). The obtained hydrolysates were employed as the substrate in producing L-LA by separate hydrolysis and fermentation (SHF). The maximum glucose yield (97.75 %) was achieved using UMSHs pretreated ECRs with 40 wt% ZnCl2 at 80 °C for 2 h and followed with DAH. The optimum glucose to L-LA yield obtained for SHF was 90.08 % using 5 % (w/w) inoculum cell densities of B. coagulans ATCC 7050 with yeast extract (YE). A comparable performance (89.65 %) was obtained using a nutrient combination (lipid-extracted Chlorella vulgaris residues (CVRs), vitamin B3, and vitamin B5) as a partial alternative for YE.